Nurses and Service Quality at Regional General Hospitals (RSUD) Across Sumatera Utara Province - Nilawati Nilawati; Murni Noviani Nasution; Balqis Nurmauli Damanik (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The delivery of healthcare services in Regional General Hospitals (RSUD) across Sumatera Utara Province faces significant challenges due to dynamic population growth. This study aims to analyze the relationship between nurse workload and service quality within these hospital environments. The methodology employed is a quantitative analysis based on secondary data from the 2025–2026 regional statistical reports and empirical literature reviews of various hospitals in Sumatera Utara. Research findings indicate a significant negative correlation between excessive workload and the quality of nursing care (p = 0.000). The nurse ratio in Sumatera Utara (144.35 per 100,000 population) remains below the national target of 158 per 100,000, triggering physical and mental fatigue (burnout). Decreased concentration due to administrative and temporal burdens increases the risk of Adverse Events (KTD) . The conclusion of this study emphasizes the necessity of accelerating medical record digitalization and workforce redistribution using the WISN method to maintain minimum service standards and patient safety.